Reinventing Public Service Delivery through Digital Civil Registration in Jember Regency, Indonesia - Mayasiana, Nur Aini; Asmuni, Asmuni (Jurnal Manajemen Pelayanan Publik, 2026)
Digital transformation in public administration has become a strategic priority to enhance efficiency, inclusivity, and service quality. In Indonesia, geographic dispersion and socio-economic disparities require innovative approaches that integrate technological advancement with governance reform. This study examines a strategic model for strengthening digital civil registration services in Jember Regency through the J-Lahbako application, framed within the concepts of Society 5.0 and the Reinventing Government paradigm. A qualitative method was employed using document analysis, field observations, and stakeholder interviews. The findings show that J-Lahbako improves service accessibility, reduces bureaucratic inefficiencies, and enhances inclusivity, particularly for rural communities. The analysis applies five interrelated governance dimensions: institutional readiness, performance outcomes, citizen orientation, accountability mechanisms, and organizational culture. The interaction of these dimensions demonstrates that sustainable digital transformation depends on the alignment between institutional structures, technological systems, and community participation. This study offers a novel contribution by proposing a contextual village-based digital governance model. Practically, the findings provide guidance for policymakers and practitioners in developing inclusive, adaptive, and sustainable public service reforms in rural areas.